PENGARUH VARIABEL DEMOGRAFI, KUALITAS LAYANAN, ATMOSFER TOKO PADA IMPULSE BUYING DI HYPERMART MAL - Utami, Okky Ratna; Rastini, Ni Made (E-Jurnal Manajemen; Vol 4 No 5 (2015), 2015)
Shopping is an activity that is often made public. Of all the activities undertaken consumer spending, not all of which are planned purchases. This phenomenon has attracted the attention of research, particularly in countries developed. The purpose of this study was to determine the influence of demographic variables, quality of service, atmosphere shop to impulse buying. This research was conducted at Hypermart Mal Bali Galeria. The number of samples taken 180 peoples, with the purposive sampling method. Analysis technique usedd is a mulltiple linear regression. These results indicate that demographic variables, quality of service, the atmosphere stores have a significant effect on impulse buying at Hypermart Mal Bali Galeria.
Keywords: variabel demografi, layanan, belanja